Simultaneous Measurements of Soil CO2 and CH4 Fluxes Using Laser Absorption Spectroscopy - Rachhpal S. Jassal; Cameron Webster; T. Andrew Black; Iain Hawthorne; Mark S. Johnson (Agricultural & Environmental Letters, 2016)
We present a method of simultaneously measuring soil CO and CH fluxes using a laser-based cavity ring-down spectrometer (CRDS) coupled to an automated non-steady-state chamber system. The differential equation describing the change in the greenhouse gas (GHG) mixing ratio in the chamber headspace following lid closure is solved for the condition when a small flow rate of chamber headspace air is pulled through the CRDS by an external pump and exhausted to the atmosphere. The small flow rate allows calculation of fluxes assuming linear relationships between the GHG mixing ratios and chamber lid closure times of a few minutes. We also calibrated the chambers for effective volume () and show that adsorption of the GHGs on the walls of the chamber caused to be 7% higher than the geometric volume, with the near-surface soil porosity causing another 4% increase in .